An evaluation of the millennium development goals and their impact on education - Isabel Carrillo Flores (Pontificia Universidad Católica del Perú, 2016)
This article analyses the status of education as a fundamental right. The recent economic crisis and associated austerity policies have worsened the situation and, rather than diminish, educational inequalities have in fact increased. Firstly, the significance of education as a Human Right is examined. Secondly, the extent to which the MDGs have been met is reviewed, particularly with regard to education, where, as detailed in various reports produced by NGOs and by the United Nations, certain difficulties have impeded their being met. The Right to Education is examined in a projective way as a right that should not be limited to the vision contained in the new Sustainable Development Goals for 2030. It is necessary to go still further and advance towards a true democratisation of education.